Biomasa Karbon Below Ground Paraserianthes Falcataria (L.) Nielsen pada Lahan Agroforestri Tradisional di Distrik Aimas, Sorong - Ohorella, Syarif; Siburian, Rima H; Febriadi, Ihsan (Median : Jurnal Ilmu Ilmu Eksakta, 2024)
Forests as part of the environment have a big role in maintaining ecosystem stability. One of them is as a carbon store. Vegetation in forests can prevent the release of carbon into the atmosphere through the process of photosynthesis where vegetation absorbs CO2 then breaks it down and stores it in the form of biomass. This is what makes it important for forest friends to study their ability to store biomass and carbon specifically on Agroforestry land as one of the site level forest management units. The aim of this research is to develop an allometric equation model to estimate the value of carbon biomass stored in bellow ground specifically for stands on traditional agroforestry land. The method used is a destructive sampling by selecting sample trees purposively and selecting three samples. trees with different diameters at breast height (dbh) but the same age representing stands on agroforestry land in Aimas District, Sorong Regency. biomass and carbon measurements were carried out through laboratory tests. The total below ground biomass content of the 19 of Paraserianthes falcataria stands obtained was 0.369 tons/ha. The below ground carbon content of sengon stands on 2.8 hectares of agroforestry land is 0.184 tonnes C/ha.